STRUKTUR MODAL, LIKUIDITAS DAN HARGA SAHAM (Penelitian Pada Perusahaan Telekomunikasi Tahun 2018-2020) - Irwin Gunawan Sahala Subiyanto; Lita Novia Ciputri (Jurnal Terapan Ilmu Manajemen dan Bisnis (JTIMB), 2022)
The company's performance reflects the condition of the company. There are two independent variables for this study, namely Capital Structure and Liquidity, while the independent variable is Stock Price. This study uses informasi on the financial statements of telecommunications companies listed on the Indonesia Stock Exchange in 2018-2020, with a total of 27 informasi using a purposive sample. Informasi processing is carried out using SPSS. The findings of this study are partially between Capital structure and Liquidity which has no effect on stock prices. Simultaneously, there is no effect on Capital Structure and Liquidity on Stock Prices.